In vitro cellular bioactivities of Maillard reaction products from sugar-gelatin hydrolysate of unicorn leatherjacket skin system. (May 2016) - Karnjanapratum, Supatra; O'Callaghan, Yvonne C.; Benjakul, Soottawat; O'Brien, Nora M.
Highlights: Maillard reaction products (MRP) from hydrolysate showed in vitro cellular bioactivities. H2 O2 -induced DNA damage was reduced by almost 50% at 1500 µg/mL MRP. MRP induced cellular antioxidant enzymes activities against H2 O2 -challenged cells. MRP reduced pro-inflammatory cytokines and nitric oxide secretion in LPS-induced cells. MRP inhibited the proliferation of colon carcinoma cells with an IC50 of 1.7 mg/mL. Abstract: The effects of Maillard reaction products (MRP), produced from galactose and a gelatin hydrolysate which was derived from unicorn leatherjacket skin, on in vitro cellular antioxidant activity, immunomodulatory properties and anti-cancer activity were investigated. MRP (750–1500 µg/mL) protected against H2 O2 -induced DNA damage in U937 cells. DNA damage was reduced by approximately 50% at the highest MRP concentration (1500 µg/mL). The activities of cellular antioxidant enzymes, superoxide dismutase (SOD) and catalase (CAT) were decreased in HepG2 cells exposed to H2 O2 but were induced in the presence of MRP. MRP reduced the production of pro-inflammatory cytokines (IL-1β and IL-6) and nitric oxide in LPS-induced RAW264.7 cells. The proliferation of colon carcinoma, Caco-2 cells was inhibited in the presence of MRP with an IC50 of 1.7 mg/mL. Therefore, MRP demonstrated bioactive potential through the suppression of oxidative stress and inflammation in vitro in addition to inhibiting the proliferation of human colon cancer cells.